Persepsi - Ananda Hulwatun Nisa; Hidayatul Hasna; Linda Yarni (Universitas Pahlawan Tuanku Tambusai, 2023)
Humans as creatures who are born with perfection have the cognitive ability to process information from the surrounding environment. This ability is influenced by factors such as intelligence level, physical condition, and the speed of the information processing system. Cognitive limitations can occur due to problems or disturbances in cognitive abilities, either from birth or due to changes in the human body. This research uses a qualitative descriptive method approach with a focus on literature study. The research results discuss the concept of perception, outlining definitions from various experts, such as Stephen P. Robbins, Kinichi and Kreitne, McShane and Von Glinow, and others. Perception is understood as a complex process involving the recognition, organization, and interpretation of information through the five senses. In its analysis, the research highlights the perception process involving the stages of selection, organization, and interpretation. Selection involves choosing information that attracts attention, organization refers to the arrangement of information in a cognitive structure, and interpretation is the assignment of meaning to information. Research also explains that perception is not only limited to physical objects, but also involves perception of humans. Factors such as objects, sensory organs, attention, and perception processes play a role in forming an individual's impression and assessment of the surrounding environment. In conclusion, this research highlights the complexity of perceptual processes and their relevance in shaping human understanding and interaction with the environment. The importance of understanding perception has implications in various contexts, including psychology, social interaction, and self-development. The results of this study contribute to our understanding of how humans process and assign meaning to information from their environment.